Serum Prostate Specific Antigen level in Women with Polycystic Ovary Syndrome - Ibrahim, Wasan W.; Salah, Raya Kh.; Abbas, Widad M. (Journal of the Faculty of Medicine Baghdad, 2016)
Background: Polycystic ovary syndrome (PCOS) is a common disorder in women in the reproductive age associated with disturbance of reproductive, endocrine and metabolic functions. The pathophysiology of PCOS appears to be multifactorial and polygenic. Objective: To measure the level of prostate –specific antigen (PSA) and to evaluate the value of prostatic specific antigen as a marker of hyperandrogenism in women with PCOS. Patients and Methods: One hundred women were entrolled in this study, 50 women were PCOS group and the remainder was healthy women served as control group. Hormonal profile (serum testosterone, luteinizing hormone (LH), follicle stimulating hormone (FSH) levels were measured. Ferriman-Gallway Score (FGS) was assessed. Serum prostate specific antigen level was measured in both groups. Correlation between PSA level and (LH/FSH, testosterone and FGS) were evaluated. Result: Mean serum PSA level was significantly higher in PCOS women compared to control women (0.15+0.09, 0.016+0.003) respectively with P value < 0.05 ). Serum PSA level in women with PCOS had significant positive correlation with FGS, LH/FSH ratio and serum testosterone with r values: 0.964, 0.988, 0.922 respectively. There was a strong correlation between serum PSA levels with the degree of hirsutism as evaluated by Ferriman –Gallway score . Serum PSA level in the 1st group ( 4-8 ) was 0.07+0.009, in the 2 nd group ( FGS9-12 ) was 0.1+0.06 and in the 3 rd group ( FGS 13-16 ) was 0.3+0.03 . Conclusion: Prostate – specific antigen level is significantly higher in women with PCOS and correlate positively with LH/FSH, testosterone and Ferriman-Gallway score. It is also concluded that the higher score of hirsutism correlate with the higher serum PSA level.